Soluble CD146, a novel endothelial marker, is increased in physiopathological settings linked to endothelial junctional alteration - Bardin, Nathalie; Moal, Valérie; Anfosso, Francine; Daniel, Laurent; Brunet, Philippe; Sampol, José; George, Françoise Dignat (Thrombosis and Haemostasis, 2003)
CD146, a novel cell adhesion molecule localized at the endothelial junction, is involved in the control of cell-cell cohesion. It is found as a soluble form in conditioned medium of cultured endothelial cells. We developed an ELISA and report for the first time the presence of a soluble form of CD146 (sCD146) in the plasma of healthy subjects. Mean sCD146 values (260 ± 60 ng/ml) were higher in subjects over 50 years and in men. We therefore investigated sCD146 values in patients with chronic renal failure (CRF), a clinical setting associated with junctional alterations. A significant increase in sCD146 was found in patients with CRF matched with controls (457 ± 181 ng/ml versus 288 ± 82 ng/ml respectively, p<0.0001). This increase was corroborated by increased endothelial expression of CD146 on kidney biopsies from patients with CRF. In contrast, in patients with CRF no modulation was observed for the soluble and cell-associated form of CD31, another junctional molecule. Together these data indicate that sCD146 circulates in the plasma of healthy subjects. Modifications of its basal levels could reflect alterations of junctional functions such as vascular permeability.
Keywords: CD146; endothelial cells; endothelial junction; soluble endothelial marker; chronic renal failure